Sustainable Clean Energy Solution for Bangladesh. Green Technology Attribute for a Sustainable Energy, Economy and Environment - Shahidul, Islam; Iqbal M., Muitaba; Shahnur, Begum (TFE Global Sdn Bhd, 2025)
The book Sustainable Clean Energy Solution for Bangladesh offers a strategic roadmap for transitioning from hazardous fossil fuels to renewable energy for achieving both economic prosperity and ecological sustainability. The current reliance on approximately 17,500 MW of fossil fuels to power Bangladesh's economic activities carries significant environmental, public health, and biodiversity costs. Annually, this combustion releases an estimated 68 million tonnes of carbon emission (CO,eq), leading to severe air, water, and soil pollution. Atmospheric pollution, characterized by elevated levels of particulate matter (PM), nitrogen oxides (NOx), sulphur dioxide (SO2), and other hazardous air pollutants, drastically impairs air quality. This directly contributes to a surge in respiratory illnesses, cardiovascular diseases, and carcinogenic risks within the population, with studies indicating a significant burden of premature deaths and reduced life expectancy attributable to air pollution alone. Furthermore, industrial discharges, including heavy metals and thermal effluents from fossil fuel power plants, contaminate vital water resources, damaging delicate aquatic ecosystems and potentially introducing toxins into the food chain. Soil degradation, exacerbated by acid rain deposition and the accumulation of ash and combustion by-products, negatively impacts agricultural productivity, raising concerns about food security. The continued dependence on fossil fuels also precipitates biodiversity loss through habitat destruction linked to energy infrastructure development and resource extraction. The weakening of ecosystems due to air and water pollution diminishes their resilience to environmental stressors. Moreover, the overarching impact of climate change, driven predominantly by greenhouse gas emissions from fossil fuels, manifests as rising sea levels, intensified extreme weather events, and altered habitats, posing a grave threat to Bangladesh's diverse flora and fauna, including iconic endangered species. This book serves as a wakeup call to action, advocating for the urgent and comprehensive utilization of Bangladesh's abundant renewable energy resources. By embracing sustainable clean energy solutions, Bangladesh can safeguard public health, protect its invaluable environment, and pave the way for a truly sustainable future.